A new species of Chaetonerius Hendel (Diptera: Neriidae) from Northeast Madagascar - Sepúlveda, Tatiana A.; de S. Souza, Diego (Zootaxa, 2019)
A new species of Ethiopian Neriidae, Chaetonerius serratus sp. n., is described from Madagascar. Differential characters are provided along with photographs and illustrations of the type material, including details of the male genitalia. The key for identification of Chaetonerius Hendel from the East African islands provided by Sepúlveda & de Carvalho (2019) is modified to include the new species.